Battery preparation method and battery

By adding pore-forming agent as an electrolyte component to the lithium-ion battery pole slurry to form pores, the problems of reduced power density and increased polarization caused by high compaction are solved, and the fast charging capacity and energy density are improved, while reducing the risk of lithium extraction and improving production efficiency.

CN120453509APending Publication Date: 2025-08-08ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510509959.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

In the process of pursuing high energy density, high compaction leads to a decrease in power density and an increase in polarization, and an increase in the thickness of the electrode sheet leads to insufficient utilization of active substances. The existing pore design method increases the manufacturing difficulty or affects the uniformity of the electrode compaction density.

Method used

The pore-forming agent is added to the positive electrode or negative electrode slurry, making it one of the electrolyte components, forming pores on the electrode sheet, improving wetting properties and lithium ion transport paths, and forming pore-forming agent by injecting the electrolyte.

Benefits of technology

It improves the fast charging capacity and energy density of the battery, reduces the risk of lithium extraction, and eliminates the need for additional processes and equipment, improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120453509A_ABST
    Figure CN120453509A_ABST
Patent Text Reader

Abstract

The invention discloses a battery preparation method and a battery, and relates to the technical field of battery preparation. The preparation method of the battery specifically comprises the following steps: preparing positive electrode slurry and negative electrode slurry; coating the surface of a current collector with the prepared positive electrode slurry and negative electrode slurry, and drying to obtain a positive plate and a negative plate; rolling and cutting the obtained positive plate and negative plate, and then assembling into a soft package dry battery cell; baking the soft package dry battery core, injecting electrolyte for infiltration, forming, aging and grading capacity to obtain a finished battery, and adding a pore-forming agent belonging to one of electrolyte components into the positive electrode slurry or / and the negative electrode slurry in the process of preparing the positive electrode slurry and the negative electrode slurry; the pore-forming agent is dissolved in the electrolyte in the electrolyte injection infiltration process, and pores are formed in the positive plate or / and the negative plate in the dissolving process. According to the invention, the pores can be formed in the pole piece without adding extra pore-forming process and equipment, so that the fast charging capacity and the energy density of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery manufacturing, and in particular to a battery preparation method and a battery. Background Art

[0002] Currently, lithium-ion batteries pursue high energy density by increasing electrode thickness and compaction density. However, this strategy also has limitations. High compaction leads to reduced power density and poor electrode wetting, while electrode thickness cannot be increased indefinitely. Excessively thick electrodes can lead to increased battery polarization and inadequate utilization of the active material at the bottom.

[0003] Later, it was discovered that improving the fast-charging capability of lithium-ion batteries can reduce charging time and alleviate concerns about insufficient energy density. Currently, the main measures to improve the fast-charging performance of lithium-ion batteries include reducing the thickness of the pole pieces, using power-type electrode materials (including amorphous carbon, lithium titanate, expanded graphite, and materials with smaller particle sizes), and using electrolytes with higher ionic conductivity, lower viscosity, and better film-forming properties. However, these methods also have their own drawbacks. For example, reducing the thickness of the pole pieces will significantly reduce the energy density; using materials such as amorphous carbon and lithium titanate will increase manufacturing costs; and smaller particle size electrode materials may also lead to a decrease in the first effect (initial charge and discharge efficiency).

[0004] Later, it was discovered that a reasonable design of the gaps in the pole pieces can reduce battery polarization and improve the fast charging capability of the battery, and reduce the performance deterioration caused by the increase in pole piece thickness and compaction. However, the current pole piece gap design method also has some defects. For example, patent CN 111710833 A discloses a technology for creating pores on the electrode surface using a laser, but this increases the difficulty of manufacturing and makes it difficult to avoid the loss of active substances. Patents CN116565144A, CN116544355A, and CN116315132A modify the rolling equipment to create grooves during the rolling process to improve the liquid storage capacity. This involves modifications to existing equipment and will cause uneven electrode compaction density. Summary of the Invention

[0005] In order to solve the above problems, the present invention provides a battery preparation method and a battery. By adding a pore-forming agent, pores can be formed on the electrode, thereby improving the wettability of the electrode, shortening the transmission path of lithium ions, and improving the fast charging capability of the battery. The pore-forming agent is one of the components of the electrolyte, and no additional processes and equipment are required, thereby improving production efficiency.

[0006] The present invention provides a method for preparing a battery, comprising the following steps: Prepare positive electrode slurry and negative electrode slurry; apply the prepared positive electrode slurry and negative electrode slurry on the surface of the current collector and dry to obtain positive electrode sheets and negative electrode sheets; roll and cut the obtained positive electrode sheets and negative electrode sheets, and then assemble them into soft-package dry battery cells; bake the soft-package dry battery cells, inject electrolyte for infiltration, form, age, and separate the capacity to obtain finished batteries, wherein, in the process of preparing the positive electrode slurry and negative electrode slurry, a pore-forming agent that is one of the components of the electrolyte is added to the positive electrode slurry and / or the negative electrode slurry; in the process of injecting electrolyte for infiltration, the pore-forming agent dissolves in the electrolyte, and forms pores on the positive electrode sheet and / or the negative electrode sheet during the dissolution process.

[0007] In one embodiment of the present invention, during the coating process, the side of the positive electrode slurry or / and the negative electrode slurry containing a low content of the pore former is coated on the current collector.

[0008] In one embodiment of the present invention, the pore-forming agent includes a high melting point solvent, an additive, and a lithium salt.

[0009] In one embodiment of the present invention, the solvent includes one or more of ethylene carbonate, trimethylene carbonate, cyclopentane, malononitrile, tetrahydrofuran, 2-methyl-1,3-dioxolane, and propyl butyrate; the additive includes one or more of vinylene carbonate and lithium cyclodifluorophosphate; and the lithium salt includes one or more of lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).

[0010] In one embodiment of the present invention, the solubility of the pore former in the electrolyte is >10 mmol / L.

[0011] In one embodiment of the present invention, the mass proportion of the pore former in the positive electrode slurry and / or the negative electrode slurry is 0.05% to 50%.

[0012] In one embodiment of the present invention, the porosity of the positive electrode sheet or / and the negative electrode sheet can be adjusted by adding the amount of the pore former to the positive electrode slurry or / and the negative electrode slurry; the porosity percentage of the positive electrode sheet or the negative electrode sheet H=(1-K)×m / p / v, wherein m is the mass of the pore former in the positive electrode sheet or / and the negative electrode sheet, p refers to the density of the pore former in the positive electrode sheet or / and the negative electrode sheet, v refers to the volume of the positive electrode sheet or / and the negative electrode sheet, K is the loss coefficient of the pore former in the preparation of the positive electrode sheet or / and the negative electrode sheet, 0 <K<1。

[0013] In one embodiment of the present invention, the amount of the pore-forming agent in the electrolyte needs to be adjusted accordingly according to the amount of the pore-forming agent in the positive electrode slurry or / and the negative electrode slurry; the mass of the corresponding pore-forming agent in the electrolyte is C=B-(1-K)×A, where A refers to the total mass of the pore-forming agent added to the positive electrode slurry or / and the negative electrode slurry, B refers to the theoretical mass of the same substance of the corresponding pore-forming agent in the electrolyte, and K is the loss coefficient of the pore-forming agent in preparing the positive electrode sheet or / and the negative electrode sheet, 0 <K<1。

[0014] In one embodiment of the present invention, the positive electrode slurry includes one or more of lithium iron phosphate, ternary, lithium cobalt oxide, lithium manganese oxide, layered sodium oxide, sodium ion battery polyanion, Prussian blue analogues, and lithium-rich manganese; the negative electrode slurry includes one or more of graphite, silicon carbon, silicon, hard carbon, soft carbon, mesophase carbon microspheres, expanded graphite, and phosphorus.

[0015] The present invention also provides a battery, which is prepared by the battery preparation method described above.

[0016] Compared with the existing technology, the present invention has the following beneficial technical effects: The present invention provides a method for preparing a porous electrode. By adding a pore-forming agent to the positive electrode slurry and / or the negative electrode slurry, pores can be formed on the electrode sheet, thereby improving the wettability of the electrode sheet, shortening the transmission path of lithium ions, and thereby improving the fast charging capability and energy density of the battery. The pore-forming agent is one of the main components of the electrolyte, has good solubility with the electrolyte, and has no negative impact on the battery. The corresponding pore-forming agent can be selected according to different electrolyte components. The porosity of the electrode sheet can be adjusted by the amount of pore-forming agent added, without the need for additional pore-forming processes and equipment, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart of a battery preparation method. DETAILED DESCRIPTION

[0018] The following embodiments of the present invention are described in further detail with reference to the accompanying drawings and examples. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0019] In the description of the present invention, it should be noted that the orientations or positional relationships indicated in this description are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred parts or elements must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0020] See also Figure 1 The present invention provides a method for preparing a battery, comprising the following steps: The first step is to prepare positive electrode slurry and negative electrode slurry; in addition to the positive electrode active material, conductive agent, binder and solvent, a certain proportion of pore former is added to the positive electrode slurry, and in addition to the negative electrode active material, conductive agent, binder and solvent, a certain proportion of pore former is also added to the negative electrode slurry. The content of the pore former in the two slurries is different, but the other operations and process parameter requirements are consistent with the process of preparing the slurry in the prior art; it is also possible to add a certain proportion of pore former only to the positive electrode slurry or the negative electrode slurry; the positive electrode slurry is suitable for various lithium / sodium / potassium-containing materials, including but not limited to lithium iron phosphate, ternary, lithium cobalt oxide, lithium manganese oxide, layered sodium oxide, sodium ion battery polyanion, Prussian blue analogues, lithium-rich manganese; the negative electrode slurry is suitable for including but not limited to one or more of graphite, silicon carbon, silicon, hard carbon, soft carbon, mesophase carbon microbeads, expanded graphite, and phosphorus; In the second step, the prepared positive electrode slurry and negative electrode slurry are respectively coated on the surface of the positive current collector and the negative current collector, and dried to obtain the positive electrode sheet and the negative electrode sheet; during the coating process, the side with low pore-forming agent content in the positive electrode slurry or / and the negative electrode slurry is coated on the current collector, so as to ensure that the porosity at the bottom of the electrode sheet is lower than that at the top after the pore-forming agent is dissolved. In addition, in thick electrodes, it is difficult to wet the bottom of the electrode sheet. If too much pore-forming agent is added to the bottom of the electrode sheet, the gap at the bottom of the electrode sheet will be too large, the structure will collapse, and the adhesion between the active material and the current collector may be low, resulting in material falling off and demolding; the drying process can be carried out according to the parameters of the conventional battery cell manufacturing scheme in the prior art; The third step is to roll-press and cut the obtained positive and negative electrode sheets and assemble them into soft-pack dry cells. The rolling and cutting are carried out according to the parameters of the conventional cell manufacturing plan. The fourth step is to bake the soft-pack dry cell, inject the electrolyte for infiltration, form, age, and separate the capacity to obtain a finished battery; the electrolyte also includes a pore-forming agent, which is one of the main components of the electrolyte. The pore-forming agent can be dissolved in the electrolyte and can form pores on the positive and negative electrodes during the dissolution process. The battery assembly and injection steps are consistent with the conventional process, and the formation, aging, and capacity separation processes are all consistent with the conventional process. Since the pore-forming agent is one of the main components of the electrolyte, in order to maintain the content of each component in the final electrolyte unchanged, the amount of pore-forming agent in the electrolyte needs to be adjusted accordingly according to the amount of pore-forming agent used.

[0021] The present invention adds a pore-forming agent to the positive electrode slurry and / or the negative electrode slurry, and the pore-forming agent can be dissolved in the electrolyte. During the dissolution process, pores can be formed on the positive electrode sheet and / or the negative electrode sheet. The presence of the pores can improve the wettability of the positive electrode sheet and / or the negative electrode sheet, shorten the transmission path of lithium ions, and thereby improve the fast charging capability of the battery. The pore-forming agent is one of the main components of the electrolyte. During the manufacturing process, no additional steps and equipment are required, which can improve the battery production efficiency.

[0022] Since the pore former is one of the main components of the electrolyte, and the conventional components of the electrolyte include organic solvents, additives, and lithium salts, therefore, the pore former in the present invention also includes solvents, additives, and lithium salts. Also, since the pore former needs to be soluble in the electrolyte, in the present invention, solvents, additives, and lithium salts with high melting points (melting points higher than 2000 °C) need to be selected. Generally, solvents, additives, and lithium salts are solid powder materials at room temperature. Specifically, the solvents include one or more of ethylene carbonate, trimethylene carbonate, sulfolane, malononitrile, tetrahydrofuran, 2-methyl-1,3-dioxolane, and propyl butyrate; the additives include one or more of vinylene carbonate and lithium difluorophosphate; the lithium salts include one or more of lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, and lithium difluoro bis(oxalato)phosphate.

[0023] If the solubility of the pore former in the electrolyte is too small, the pore-forming effect will not be obvious, and naturally, the effect of improving the fast charging ability of the battery cannot be achieved. Therefore, the solubility of the pore former in the electrolyte in the present invention is > 10 mmol / L, and the mass ratio of the pore former in the positive electrode paste is 0.05% - 50%, and the mass ratio of the pore former in the negative electrode paste is also 0.05% - 50%, preferably 2% - 10%, for example, 2%, 3%, 5%, 10%. If it is lower than 0.05%, due to the too small content, the pore-forming phenomenon will not be obvious. If it is higher than 50%, it will cause the binding between adjacent particles and between the current collector to weaken, resulting in the diaphragm peeling off during the cycling of the battery cell.

[0024] It should be noted that the porosity of the positive electrode sheet or / and the negative electrode sheet in the present invention can be adjusted by the addition amount of the pore former in the positive electrode paste or / and the negative electrode paste. Specifically, the porosity H of the positive electrode sheet or / and the negative electrode sheet = (1 - K) × m / p / v, where m is the mass of the pore former added in the positive electrode sheet or / and the negative electrode sheet, p is the density of the pore former in the positive electrode sheet or / and the negative electrode sheet, v is the volume of the positive electrode sheet or / and the negative electrode sheet, and K is the loss coefficient of the pore former during the preparation of the positive electrode sheet or / and the negative electrode sheet, and 0 < K < 1. The present invention can adjust the porosity of the electrode sheet by adjusting the usage amount of the pore former while keeping the components of the electrolyte unchanged.

[0025] Since the pore former is one of the main components of the electrolyte, to keep the content of each component in the final electrolyte unchanged, it is necessary to make corresponding adjustments to the amount of the pore former in the electrolyte according to the usage amount of the pore former in the positive electrode paste or / and the negative electrode paste. Specifically, the mass C of the corresponding pore former in the electrolyte = B - (1 - K) × A, where A is the total mass of the pore former added in the positive electrode paste or / and the negative electrode paste, B is the theoretically required mass of the same substance of the pore former in the electrolyte, and K is the loss coefficient of the pore former during the preparation of the positive electrode sheet or / and the negative electrode sheet, and 0 < K < 1.

[0026] The present invention also provides a battery, which is prepared by the battery preparation method described above.

[0027] The present invention is further described in detail below with reference to the examples. In the following examples, ethylene carbonate (EC) is used as a pore-forming agent, and other pore-forming agents can be used for reference: Comparative Example 1 In this comparative example, an LFP-Gr system battery was selected. The positive electrode sheet was prepared by mixing LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) in a mass ratio of 96:2:2 into a slurry, and the mixed slurry was evenly coated on an aluminum foil current collector. After drying, the mixed slurry was rolled, slit and die-cut to obtain a positive electrode sheet; the negative electrode sheet was prepared by mixing graphite, conductive carbon black, styrene-butadiene rubber and sodium hydroxycellulose (CMC) in a mass ratio of 96:1:1.8:1.2 to obtain a mixed slurry; the mixed slurry was evenly coated on a copper current collector, and after drying, the mixed slurry was rolled, slit and die-cut to obtain a negative electrode sheet; the battery cell was prepared by a stacking method to produce a 2.61Ah small soft-pack battery. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 35%: 20%: 25%: 3%: 1%: 1%: 15%, and the injection coefficient is 3.5. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% residual capacity (SOC) at a constant current of 0.04C.

[0028] Example 1 In this example, an LFP-Gr system battery is selected. The positive electrode sheet is prepared by mixing LFP (Lithium Iron Phosphate), conductive carbon Super P, and polyvinylidene fluoride (PVDF) in a mass ratio of 96:2:2 into a slurry, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit, and die-cut to obtain a positive electrode sheet; the negative electrode sheet is prepared by mixing graphite, conductive carbon black, styrene-butadiene rubber, sodium hydroxycellulose (CMC), and ethylene carbonate (EC) in a mass ratio of 94:1:1.8:1.2:2; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit, and die-cut to obtain a negative electrode sheet; the battery cell is prepared by a lamination method to produce a 2.61Ah small soft-pack battery. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 33.4%: 20.49%: 25.62%: 3.07%: 1.02%: 1.02%: 15.37%, and the injection coefficient is 3.42. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0029] Example 2 In this example, an LFP-Gr system battery is selected. The positive electrode sheet is prepared by mixing LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) in a mass ratio of 96:2:2 into a slurry, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the negative electrode sheet is prepared by mixing graphite, conductive carbon black, styrene-butadiene rubber, sodium hydroxycellulose (CMC) and ethylene carbonate (EC) in a mass ratio of 92:1:1.8:1.2:4; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the battery cell is prepared by a lamination method to produce a 2.61Ah small soft-pack battery. An electrolyte was injected into an argon glove box. The mass ratio of each substance in the electrolyte was ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 31.64%: 21.03%: 26.29%: 3.16%: 1.05%: 1.05%: 15.78%, and the injection coefficient was 3.33. Then, after vacuum packaging, standing, formation, and shaping, a battery cell was obtained. Among them, the formation treatment was to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0030] Example 3 In this embodiment, an LFP-Gr system battery is selected. The positive electrode sheet is prepared by mixing LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) in a mass ratio of 96:2:2 into a slurry, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the negative electrode sheet is prepared by mixing graphite, conductive carbon black, styrene-butadiene rubber, sodium hydroxycellulose (CMC) and ethylene carbonate (EC) in a mass ratio of 90:1:1.8:1.2:6; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the battery cell is prepared by a lamination method to produce a 2.61Ah small soft-pack battery. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 29.7%: 21.63%: 27.04%: 3.24%: 1.08%: 1.08%: 16.22%, and the injection coefficient is 3.24. Then, after vacuum packaging, standing, formation, and shaping, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0031] Example 4 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) are mixed into a slurry in a mass ratio of 96:2:2, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) = mixed in a mass ratio of 88:1:1.8:1.2:8; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.61Ah small soft-pack battery is made by a lamination method. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 27.56%: 22.29%: 27.86%: 3.34%: 1.11%: 1.11%: 16.72%, and the injection coefficient is 3.14. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0032] Example 5 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) are mixed into a slurry in a mass ratio of 96:2:2, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) = mixed in a mass ratio of 86:1:1.8:1.2:10; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.61Ah small soft-pack battery is made by the lamination method. An electrolyte was injected into an argon glove box. The mass ratio of each substance in the electrolyte was ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 25.16%: 23.03%: 28.78%: 3.45%: 1.15%: 1.15%: 17.27%, and the injection coefficient was 3.04. Then, after vacuum packaging, standing, formation, and shaping, a battery cell was obtained. Among them, the formation treatment was to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0033] Example 6 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) are mixed into a slurry in a mass ratio of 96:2:2, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) = mixed in a mass ratio of 81:1:1.8:1.2:15; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.61Ah small soft-pack battery is made by a lamination method. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 17.79%: 25.29%: 31.62%: 3.79%: 1.26%: 1.26%: 18.97%, and the injection coefficient is 2.77. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0034] Example 7 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P, polyvinylidene fluoride (PVDF), and EC are mixed into a slurry in a mass ratio of 94:2:2:2, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit, and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) are mixed in a mass ratio of 92:1:1.8:1.2:4; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit, and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.56Ah small soft-pack battery is made by a lamination method. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 28.37%: 22.04%: 27.55%: 3.31%: 1.1%: 1.1%: 16.53%, and the injection coefficient is 3.18. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0035] Example 8 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P, polyvinylidene fluoride (PVDF) and EC are mixed into a slurry in a mass ratio of 92:2:2:4, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) = mixed in a mass ratio of 92:1:1.8:1.2:4; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.5Ah small soft-pack battery is made by a lamination method. An electrolyte was injected into an argon glove box. The mass ratio of each substance in the electrolyte was ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 24.6%: 23.2%: 29%: 3.48%: 1.16%: 1.16%: 17.40%, and the injection coefficient was 3.02. Then, after vacuum packaging, standing, formation, and shaping, a battery cell was obtained. Among them, the formation treatment was to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0036] Example 9 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P, polyvinylidene fluoride (PVDF), and EC are mixed into a slurry in a mass ratio of 90:2:2:6, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit, and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) are mixed in a mass ratio of 92:1:1.8:1.2:4; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit, and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.45Ah small soft-pack battery is made by a lamination method. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 20.23%: 24.55%: 30.68%: 3.68%: 1.23%: 1.23%: 18.41%, and the injection coefficient is 2.85. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% remaining capacity (SOC) at a constant current of 0.04C.

[0037] Example 10 In this embodiment, an LFP-Gr system battery is selected. The preparation of the positive electrode sheet is as follows: LFP (Lithium Iron Phosphate), conductive carbon Super P and polyvinylidene fluoride (PVDF) are mixed into a slurry in a mass ratio of 96:2:2, and the mixed slurry is evenly coated on an aluminum foil current collector. After drying, the mixed slurry is rolled, slit and die-cut to obtain a positive electrode sheet; the preparation of the negative electrode sheet is as follows: graphite: conductive carbon black: styrene-butadiene rubber: sodium hydroxycellulose (CMC): ethylene carbonate (EC) = mixed in a mass ratio of 92:1:1.8:1.2:4; the mixed slurry is evenly coated on a copper current collector, and after drying, the mixed slurry is rolled, slit and die-cut to obtain a negative electrode sheet; the preparation of the battery cell is as follows: a 2.61Ah small soft-pack battery is made by a lamination method. An electrolyte is injected into an argon glove box. The mass ratio of each substance in the electrolyte is ethylene carbonate (EC): ethylene carbonate (EMC): dimethyl carbonate (DMC): vinylene carbonate (VC): polystyrene (PS): dimethyl sulfate (DTD): lithium hexafluorophosphate (LiFP6) = 35%: 20%: 25%: 3%: 1%: 1%: 15%, and the injection coefficient is 3.5. Then, after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Among them, the formation treatment is to charge the lithium-ion secondary battery to 35% residual capacity (SOC) at a constant current of 0.04C.

[0038] The batteries prepared in Comparative Example 1 and Examples 1-10 were subjected to cycle life and lithium plating risk tests. The cycle life test method is: 2C charging to 3.75V, 2C discharging to 2.0V, and 200 cycles. The method for determining the risk of lithium plating is: charging the battery cell at -10°C according to a given step-by-step charging process, discharging at 0.33 C, and after 50 cycles, the battery is disassembled after standing for 24 hours to observe whether there is lithium plating on the surface of the negative electrode. If the lithium plating area occupies 0-5% of the entire electrode area, it is judged as low, 5-10% is judged as medium, and greater than 10% is judged as high, and the separation of the active material from the current collector is judged as demolding. The test results are shown in Table 1 below: Table 1 Test results of battery cycle life and lithium plating risk in Comparative Example 1 and Examples 1-10

[0039] Comparing Examples 1-6, 8-9 and Comparative Example 1, it can be seen that no pore-forming agent was added to the positive and negative electrode slurries in Comparative Example 1, and only the electrolyte contained a pore-forming agent. In Examples 1-6, a pore-forming agent was added to the negative electrode slurry, and in Examples 8-9, a pore-forming agent was added to both the positive and negative electrode slurries. Therefore, the porosity of the negative electrode sheets in Examples 1-6 and the positive and negative electrode sheets in Examples 8-9 was higher than that in Comparative Example 1, and the battery capacity retention rate and the cycle retention rate after 200 cycles were higher than those in Comparative Example 1, and the risk of lithium plating was also reduced. It can be seen that by adding a pore-forming agent to the positive electrode slurry or / and the negative electrode slurry, the pore-forming agent is one of the main components of the electrolyte, which can improve the fast charging capability of the battery and reduce the risk of lithium plating. From the comparison of Examples 1-6, it can be seen that the porosity of the negative electrode sheet gradually increases with the increase of the amount of pore-forming agent added, the battery capacity retention rate and the cycle retention rate of 200 cycles gradually increase, and the risk of lithium plating is also reduced. From the comparison of Example 2 and Examples 8-9, it can be seen that the porosity of the positive electrode sheet gradually increases with the increase of the amount of pore-forming agent added, the battery capacity retention rate and the cycle retention rate of 200 cycles gradually increase, and the risk of lithium plating is also reduced. Further comparing Examples 1-6 and Example 7, due to the excessive amount of pore-forming agent added in the negative electrode slurry, the bonding between the accessory particles and with the current collector is weakened, resulting in the film peeling of the battery cell during cycling, so the amount of pore-forming agent added should be appropriate; in addition, from the comparison of Example 2 and Example 10, it can be seen that since the amount of pore-forming agent in the electrolyte in Example 10 is not adjusted according to the amount of pore-forming agent in the negative electrode slurry, the amount of electrolyte additive in Example 10 is increased, resulting in an increase in the battery film formation impedance, deterioration of the kinetics, reduction of the battery capacity retention rate and the cycle retention rate of 200 cycles, and an increase in the risk of lithium plating.

[0040] From the above description, it can be known that the present invention provides a method for preparing a battery electrode battery, which can form pores on the electrode sheet by adding a pore-forming agent to the positive electrode slurry and / or the negative electrode slurry, thereby improving the wettability of the electrode sheet, shortening the transmission path of lithium ions, and thereby improving the fast charging capability and energy density of the battery. The pore-forming agent is one of the main components of the electrolyte, has good solubility with the electrolyte, and has no negative impact on the battery. The corresponding pore-forming agent can be selected according to different electrolyte components. The porosity of the electrode sheet can be adjusted by the amount of pore-forming agent added, and there is no need to add additional pore-forming processes and equipment, thereby improving production efficiency.

[0041] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical content disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A battery preparation method comprising the following steps: preparing positive electrode slurry and negative electrode slurry; Coating the prepared positive electrode slurry and negative electrode slurry on the surface of the current collector, and drying to obtain positive electrode sheets and negative electrode sheets; Roll-pressing and cutting the obtained positive electrode sheet and negative electrode sheet, and then assembling them into soft-package dry cells; The soft-pack dry cell is baked, injected with electrolyte for infiltration, formed, aged, and capacity divided to obtain a finished battery, which is characterized by: During the preparation of the positive electrode slurry and the negative electrode slurry, a pore former that is one of the components of the electrolyte is added to the positive electrode slurry and / or the negative electrode slurry; During the process of injecting the electrolyte and infiltrating, the pore-forming agent dissolves in the electrolyte and forms pores on the positive electrode sheet and / or the negative electrode sheet during the dissolution process.

2. The battery preparation method according to claim 1, characterized in that: During the coating process, the positive electrode slurry or / and the negative electrode slurry having a low pore-forming agent content is coated on the current collector.

3. The battery preparation method according to claim 1, characterized in that: The pore-forming agent includes a high-melting-point solvent, an additive, and a lithium salt.

4. The battery preparation method according to claim 2, characterized in that: The solvent includes one or more of ethylene carbonate, trimethylene carbonate, sulfolane, malononitrile, tetrahydrofuran, 2-methyl-1,3-dioxolane, and propyl butyrate; The additives include one or more of vinylene carbonate and lithium cyclodifluorophosphate; The lithium salt includes one or more of lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).

5. The battery preparation method according to claim 1, characterized in that: The solubility of the pore-forming agent in the electrolyte is greater than 10 mmol / L.

6. The battery preparation method according to claim 1, characterized in that: The mass proportion of the pore former in the positive electrode slurry and / or the negative electrode slurry is 0.05% to 50%.

7. The battery preparation method according to claim 1, characterized in that: The porosity of the positive electrode sheet and / or the negative electrode sheet can be adjusted by adding the pore-forming agent to the positive electrode slurry and / or the negative electrode slurry; The porosity percentage of the positive electrode sheet or the negative electrode sheet is H=(1-K)×m / p / v, Wherein m is the mass of the pore-forming agent in the positive electrode sheet or / and the negative electrode sheet, p refers to the density of the pore-forming agent in the positive electrode sheet or / and the negative electrode sheet, v refers to the volume of the positive electrode sheet or / and the negative electrode sheet, K is the loss coefficient of the pore-forming agent in preparing the positive electrode sheet or / and the negative electrode sheet, 0 <K<1。 8. The battery preparation method according to claim 1, characterized in that: The amount of the pore-forming agent in the electrolyte needs to be adjusted accordingly according to the amount of the pore-forming agent in the positive electrode slurry and / or the negative electrode slurry; The mass of the corresponding pore-forming agent in the electrolyte is C=B-(1-K)×A, A refers to the total mass of the pore-forming agent added to the positive electrode slurry or / and the negative electrode slurry, B refers to the theoretical mass of the same substance of the corresponding pore-forming agent in the electrolyte, K is the loss coefficient of the pore-forming agent in preparing the positive electrode sheet or / and the negative electrode sheet, 0 <K<1。 9. The battery preparation method according to claim 1, characterized in that: The positive electrode slurry includes one or more of lithium iron phosphate, ternary, lithium cobalt oxide, lithium manganese oxide, layered sodium oxide, sodium ion battery polyanion, Prussian blue analogues, and lithium-rich manganese; The negative electrode slurry includes one or more of graphite, silicon carbon, silicon, hard carbon, soft carbon, mesophase carbon microbeads, expanded graphite, and phosphorus.

10. A battery, characterized in that: The battery is prepared by the battery preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Battery preparation method

    CN116315132A

  • Preparation method of high-capacity battery pole piece

    CN116544355A

  • Preparation method of battery thick pole piece

    CN116565144A